Risk-taking tournaments: theory and experimental evidence - Petra Nieken; Dirk Sliwka (Institute for the Study of Labor (IZA), 2008)
We study risk-taking behavior in a simple two person tournament in a theoretical model as well as a laboratory experiment. First, a model is analyzed in which two agents simultaneously decide between a risky and a safe strategy and we allow for all possible degrees of correlation between the outcomes of the risky strategies. We show that risk-taking behavior crucially depends on this correlation as well as on the size of a potential lead of one of the contestants. We find that the experimental subjects acted mostly quite well in line with the derived theoretical predictions.
urn:nbn:de:101:1-2008031840
Keywords: M51; 330; Tournaments; competition; risk-taking; experiment; Extensives Spiel; Arbeitskräfte; Risikopräferenz; Theorie